Good and evil in the imaginary world of J.R.R. Tolkien - Kovář, Jan (2006)
This thesis focuses on the imaginary world of J.R.R. Tolkien called Middle-earth. It tries to examine, what were the ultimate sources of Tolkiens inspiration for creating it, as well as to what extent do the events of his life reflect those in Middle-earth. Within his most famous books: The Hobbit, The Lord of the Rings, and The Silmarillion is looked for the manifestations of good or evil. Special attention is paid to Christianity, in search for possible parallels in Middle-earth. The two principles of good and evil are observed from different angles: as embodied in different beings or artifacts or as represented by different symbols